Enhancement of photocatalytic aerobic oxidation of benzyl alcohol with the incorporation of cobalt in Zn-based MOF via post-synthetic metal exchange. (15th January 2022) - Hosseini, Seyed Mohammad; Dehghan, Hossein; Safarifard, Vahid
Graphical abstract: Modified metal-organic framework TMU-22(Zn/Co), was employed for the aerobic oxidation of benzyl alcohol. The TMU-22(Zn/Co) exhibited remarkable photocatalytic activity under visible light irradiation; the oxidation yield reached almost 65% for benzyl alcohol after 3 h reaction. The results demonstrated that the prepared photocatalyst is recyclable. Highlights: The TMU-22(Zn/Co) was used as photocatalyst for oxidation of alcohols. The TMU-22(Zn/Co) composite improves the photon-generated carrier transfer. The TMU-22(Zn/Co) inhibits the electron-hole recombination rate. The TMU-22(Zn/Co) shows good photocatalytic performance in terms of reusability. Abstract: In this work to introduce Co(II) ions into TMU-22(Zn) metal–organic framework (MOF), we report a postsynthetic exchange (PSE) approach. Several analytical methods were employed to examine the exchange between Co 2+ ions and Zn 2+ ions in TMU-22(Zn) for the formation of the mixed-metal TMU-22(Zn/Co). It was found that the introduction of active Co 2+ ions into the TMU-22(Zn) framework leads to the photocatalytic activity of TMU-22(Zn/Co) for benzyl alcohol oxidation. Since Co 2+ ions were favorably substituted at positions more accessible to the substrate, the TMU-22(Zn/Co) showed superior catalytic performance. This study provides a facile method to develop mixed-metal MOFs for photocatalysis performance.